Risk sexual behavior, sexually-transmitted infections and adolescent pregnancy prevention interventions - Elviera Gamelia; Anies Anies; Bagoes Widjanarko; Zahroh Shaluhiyah (AOSIS, 2023)
Numerous nations experience a significant prevalence of adolescent pregnancies, sexually transmitted infections (STIs), and risky sexual conduct. Consequently, there is a pressing requirement for intervention programs targeting adolescent health to modify behavior. This systematic review examines the efficacy of comprehensive interventions in diverse settings for the purpose of mitigating teenage pregnancy, sexually transmitted infections (STIs), and associated sexual risk behaviors. The objective of this study was to find interventions that can effectively reduce risky sexual activity, sexually transmitted diseases, and adolescent pregnancy. Conduct a literature search from January 2008 to December 2022 using electronic databases. Keywords "teenage pregnancy" OR "teen pregnancy" OR "adolescent pregnancy", AND "maternal education", AND "randomized clinical trial", AND "risk behavior". A total of 28 articles were found to adhere to the PRISMA standards. The majority of research examined several forms of care, including school-based, individual, community, clinic, and family-based care. The bulk of the studies conducted involved follow-up assessments conducted at various intervals ranging from one month to seven years after the intervention. The participants in these research were predominantly adolescents, with ages ranging from 13 to 18 years. Application of scientific investigation in urban, suburban, and rural regions. This program has demonstrated efficiency in preventing pregnancy, promoting contraceptive utilization, reducing the incidence of STIs and HIV, modifying sexual behavior, decreasing school dropout rates, enhancing knowledge about pregnancy and sexuality, influencing attitudes towards sexuality, fostering intention to modify hazardous sexual behavior, boosting self-efficacy, and improving parent-child relationships. This article outlines fundamental patterns in interventions aimed at preventing adolescent pregnancy in multiple countries, serving as a valuable resource for health programs. The unverified efficacy can be utilized in combination with other interventions that yield a significant positive outcome.